A flexoelectricity effect-based sensor for direct torque measurement - Zhang, Shuwen; Xu, Minglong; Liu, Kaiyuan; Shen, Shengping (Journal of physics. D, Applied physics, 2015)
In this study, a direct torque sensor based on the flexoelectricity generated by un-polarized polyvinylidene fluoride (PVDF) via electromechanical coupling is developed as a novel torque measurement mechanism that does not require external electric power excitation. The sensing method is developed based on the shear strain gradient and the shear flexoelectric response of PVDF. A theoretical analysis is primarily presented for the design of the sensing structure. Then the structure of the PVDF sensing module is discussed and designed. The radius ratio of the sensing module is defined and then discussed according to the load, the strain gradient, the electrode area and the general electric charge output. The finite element method is used to analyze the mechanical properties of the designed PVDF sensing module. Then the theoretical sensitivity of the sensor is predicated as 0.9441 pC Nm−1. The experiment system setup is developed, and the sensing properties of the measurement mechanism are tested at frequencies of 0.5 Hz, 1 Hz, 1.5 Hz and 2 Hz using identical modules. The measurement range of the designed sensor is 0-1.68 Nm and the average sensitivity is measured as 0.8950 pC Nm−1. The experimental results agree well with the theoretically predicted results. These results prove that the torque sensing method based on un-polarized PVDF is suitable for measurement of dynamic torque loads with a flexoelectricity-based mechanism. When using this method, external electric power excitation of the sensing module is no longer required.